NATURE+ in India - Report 2023 & Outlook 2024 - Sikka, Alok; Rana, Jai Chand; Tripathi, Mansi; Behera, Abhijit; Joshi, Rajashree; Patil, Sanjay; V.S., Viswadev (2023)
In India, the CGIAR Initiative on Nature-Positive Solutions works in remote parts of Western India’s Maharashtra State. NATURE+ and its partners selected several sites (called clusters) for their high potential for implementing nature-positive activities to improve nutrition, climate resilience, food security and to conserve nature. People in these tribal areas also have rich traditional knowledge that is key to natural solutions.